Formation of local spin moments of 3d impurities diluted in noble and alkali metal hosts - N. Stefanou; N. Papanikolaou (Journal of Physics: Condensed Matter, 1991)
The authors investigate the formation of local spin moments of transition metal impurities diluted in free-electron-like monovalent hosts by performing self-consistent, local spin density functional calculations for all the 3d elements embedded in jellium. The magnetic behaviour of the impurity is studied systematically by varying continuously the jellium density from zero up to a critical value, at which the magnetic moment disappears. The results are in good agreement with the results of other calculations and the available experimental data.